2022
DOI: 10.1002/pssa.202200496
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Channel Thickness on Electron Confinement in MOCVD‐Grown High Breakdown Buffer‐Free AlGaN/GaN Heterostructures

Abstract: The 2D electron gas (2DEG) confinement on high electron mobility transistor (HEMT) heterostructures with a thin undoped GaN channel layer on the top of a grain‐boundary‐free AlN nucleation layer is studied. This is the first time demonstration of a buffer‐free epi‐structure grown with metal–organic chemical vapor deposition with thin GaN channel thicknesses, ranging from 250 to 150 nm, without any degradation of the structural quality and 2DEG properties. The HEMTs with a gate length of 70 nm exhibit good DC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…The results obtained from our study are compared to those reported in previous research on various types of HEMT devices, with a focus on the relationship between saturation current and critical electrical field, as shown in Figure 5, [17,20,[30][31][32][33][34][35][36][37][38][39][40][41] Prior research on GaN HEMTs has indicated that the critical electric field level typically falls within the range of approximately 1 MV cm À1 , with limitations imposed by the material's inherent physical properties. In response to these limitations, the use of an AlN buffer has been proposed as a viable alternative, as it has been shown to enhance critical electric field levels while maintaining strong current characteristics.…”
Section: Resultsmentioning
confidence: 95%
“…The results obtained from our study are compared to those reported in previous research on various types of HEMT devices, with a focus on the relationship between saturation current and critical electrical field, as shown in Figure 5, [17,20,[30][31][32][33][34][35][36][37][38][39][40][41] Prior research on GaN HEMTs has indicated that the critical electric field level typically falls within the range of approximately 1 MV cm À1 , with limitations imposed by the material's inherent physical properties. In response to these limitations, the use of an AlN buffer has been proposed as a viable alternative, as it has been shown to enhance critical electric field levels while maintaining strong current characteristics.…”
Section: Resultsmentioning
confidence: 95%
“…The RF GaN HEMT tested in this work are based on a buffer-free AlGaN/GaN on SiC epitaxy [23], [24], [25] and were processed using a production-level 0.15 µm gate length (L g ) technology. In this study, the thickness of the undoped GaN channel layer was the only variable among the samples analyzed.…”
Section: Device and Experimental Detailsmentioning
confidence: 99%
“…Some recent reports have demonstrated promising DC and RF performances of AlGaN/GaN HEMTs grown on SiC with a total thickness lower than 1 μm. [7,8] However, the large thermal expansion coefficient difference makes the growth on Si substrates even more challenging; thus, high performance with submicrometer-thick GaN HEMTs have not been proven yet to our knowledge. [9][10][11][12][13] Moreover, although AlGaN/ GaN HEMT is the most mature technology, which demonstrated outstanding power performances in the microwave range, the device downscaling for higher frequency of operation generally results in a reduced breakdown voltage degrading the overall device performances.…”
Section: Introductionmentioning
confidence: 99%